2003
DOI: 10.1021/om020505t
|View full text |Cite
|
Sign up to set email alerts
|

ansa-Zirconocenes Based on N-Substituted 2-Methylcyclopenta[b]Indoles:  Synthesis and Catalyst Evaluation in Liquid Propylene Polymerization

Abstract: Cyclopenta[b]indole-based ansa-zirconocenes were prepared and studied as catalysts for propylene polymerization. Substituted 2-methyl-4-R-1,4-dihydrocyclopenta[b]indoles (R = Ph, 7a; R = o-Tol, 7b; R = Me, 7c) were synthesized and converted into the racemic forms of the corresponding ansa-zirconocenes Me2Si(2-Me-4-R-cyclopenta[b]indolyl)2ZrCl2 (R = Ph, 10a; R = o-Tol, 10b; R = Me, 10c). The structure of 10a was determined by X-ray analysis. The effectiveness in polymerization catalysis of the metallocenes comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…At very low concentrations of aluminoxanes/12, the stereoselectivity of the catalytic system increased in the order MAO < AOO < QO < AKO. In contrast, stereoselectivity increased in the order AKO < AOO < QO at high aluminoxanes/12 [13]. Seraidaris et al [37] investigated the effect of the co-catalysts of MAO and MAO/TIBA on the tacticity of polypropylene and found that the tacticity of polypropylene with Me 2 Si(2-Me-PhInd) 2 -ZrCl 2 /MAO (Al/AMO = 2400) was lightly lower than that of Me 2 Si(2-Me-Ph-Ind) 2 −ZrCl 2 /MAO/-TIBA (Al/AMO = 1500 : 1, Al/TIBA = 900 : 1).…”
Section: Aluminate-based Co-catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…At very low concentrations of aluminoxanes/12, the stereoselectivity of the catalytic system increased in the order MAO < AOO < QO < AKO. In contrast, stereoselectivity increased in the order AKO < AOO < QO at high aluminoxanes/12 [13]. Seraidaris et al [37] investigated the effect of the co-catalysts of MAO and MAO/TIBA on the tacticity of polypropylene and found that the tacticity of polypropylene with Me 2 Si(2-Me-PhInd) 2 -ZrCl 2 /MAO (Al/AMO = 2400) was lightly lower than that of Me 2 Si(2-Me-Ph-Ind) 2 −ZrCl 2 /MAO/-TIBA (Al/AMO = 1500 : 1, Al/TIBA = 900 : 1).…”
Section: Aluminate-based Co-catalystsmentioning
confidence: 99%
“…Van Baar et al [13] reported the preparation of highly isospecific (mmmm 95.9, 95.6%) and region-specific polypropylene (0.17-0.34% imbedded regiorrors) in liquid propylene at 70…”
Section: -Symmetric Ansa-zirconcenementioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of 5,6-dimethoxyindene (36) The dimethylsilylene-bridged analogue rac-29 has been reported in the patent literature only. It was obtained by deprotonation of the dimethylsilylene-bridged ligand precursor with nBuLi and subsequent reaction of the isolated dilithium salt with ZrCl 4 in CH 2 Cl 2 to give, after workup and crystallization from the same solvent, a 3:1 rac/meso mixture in 35% yield.…”
Section: Alkoxy-substituted Group 4 Bis(indenyl)metallocenesmentioning
confidence: 99%
“…The commercial production of iPP has mainly focused on the increase in molecular weight (M w ) and isotacticity of polypropylene, as well as the increase in catalytic activity by the change of catalyst structure. [3][4][5][6] Although many elaborated catalyst structures suitable for commercial iPP have been reported, [7][8][9][10][11][12][13][14] the synthetic procedures towards such C 2 -symmetric catalysts usually require many difficult steps giving rise to the increase in catalyst costs during the course of commercialization of iPP products. The high cost has been one of the principal reasons why the portion of metallocene-iPP products is below 1% of the total iPP market.…”
Section: Introductionmentioning
confidence: 99%